Contribuições da escala de intensidade de apoio ao planejamento e prática do professor para jovens com síndrome de down - Freitas, Polyane Gabrielle de (2019)
Teaching planning is configured as an extremely important stage in the pedagogical practice of the teacher and in the teaching-learning process of students with intellectual disabilities. In this context, the Support Intensity Scale is a tool that can assist in the preparation of teaching planning, as it allows the identification of students' needs. Thus, the present study aimed to evaluate the applicability of a teaching plan based on adaptive behaviors on the scale of support intensity for young people with Down syndrome and, as specific objectives: (a) evaluate the intensity of support in behaviors adaptations of young people with Down syndrome; (b) describe the teacher's routine and pedagogical practice; (c) apply, in collaboration with the teacher, a teaching plan given the need for support; (d) evaluate the applicability of this planning according to the teacher's perspective and implications for pedagogical practice. The study followed a qualitative approach, of the action-research type. A Special Education teacher participated in the study, two young people with Down syndrome, being: a young man with 21 years of age and his father; a 19-year-old girl and her mother. The study was carried out at a Special Education school in a medium-sized city in the interior of the state of São Paulo. The following instruments were used: a classroom observation protocol; an initial semi-structured interview for a teacher; a semi-structured interview script for parents; a semi-structured interview for parents with information about young people with Down syndrome; a Support Intensity Scale - SIS for young people and a final semi-structured interview for the teacher. The data obtained were organized and analyzed in a qualitative way grouped into four categories: (a) pedagogical practice and the teacher's teaching planning; (b) the need for support in the adaptive behaviors of young people with Down syndrome; (c) preparation and application of teaching planning based on the need for support; (d) evaluation of the applicability of teaching planning from the teacher's perspective. As a result, it was found that the area in which young people with Down syndrome needed greater support was the adaptive area of lifelong learning and, furthermore, after the teaching planning developed with the teacher, it was possible to perceive positive changes in the involvement in the proposed activities, interaction with colleagues, teacher and researcher. As for teaching planning based on the SIS Scale, it was found that it can assist in the teacher's pedagogical practice, since it allowed greater centralization in the needs of young people with Down syndrome. Accordingly, it is expected that this study will serve as an example of good practices, as well as an indication for the use of the Support Intensity Scale - SIS as a tool for teaching planning. It was concluded, therefore, that teaching planning based on the SIS Scale achieved favorable effects on the learning of young people with Down syndrome in the investigated reality, thus being able to have its results considered in future research and interventions.